Intellectual property rights and access rules for germplasm: benefit or straitjacket - Ghijsen, Huib (Euphytica, 2009)
Today the free access to germplasm for breeding purposes is becoming more and more limited by two different developments: the patenting of traits and varieties on the one hand and the evolution with regard to access and benefit sharing in the convention on biological diversity (CBD) and the international treaty for plant genetic resources of food and agriculture (IT-PGRFA) on the other hand. Patents are generally more restrictive regarding research and breeding than plant breeder's rights in which the important notion of the breeder's exemption in the laws based on the international union for the protection of new varieties of plants. Conventions provides free access to commercialized, protected plant varieties for further commercial breeding. This breeder's exemption is limited by the notion of essential derivation: closely bred “essentially derived varieties” (EDV's) need for the purpose of commercialization the permission of the owner of the protected initial variety where the EDV has been derived from. New traits, from natural or artificial sources, can be protected by patents. The plants containing a patented trait do fall under its patent protection. In the USA conventional varieties can also be patented, which is not possible in most other countries in the world. This patent system allows claims on the progenies resulting from crossing patented plants with other plants. As each new variety consists of a unique combination of existing characteristics and crossing this variety with plants of other varieties yield new combinations, the ownership of a particular variety should not extend to the progenies of the crossing parents. The CBD and IT-PGRFA treaties subject the access to germplasm to particular rules for benefit sharing, whereby the terms for access under the CBD are still to be established and the outcome of the present negotiations is very uncertain. On top of these developments private companies use increasingly Material Transfer Agreements and restrictions printed on seed bags to limit the access to commercial varieties for breeding purposes. The question arises whether this tightening straitjacket will benefit or harm the breeding of new varieties in the long run and how the breeders in the field (will) cope with these developments.